Effect of Androgens, Estrogens and Progesterone on Periodontal Tissues - Bhardwaj, Amit; Bhardwaj, Shalu Verma (Journal of Orofacial Research, 2012)
Hormones are specific regulatory molecules that have potent effects on the major determinants of the development and the integrity of the skeleton and oral cavity including periodontal tissues. Sex hormones have long been considered to play an influential role on periodontal tissues, bone turnover rate, wound healing and periodontal disease progression. This review focuses on the effects of endogenous sex hormones on the periodontium and the goal is to inform and update practitioners’ knowledge about the impact of these hormones on periodontal status.